Consensus statements -optimizing performance of the elite athlete - Bangsbo, J.; Hostrup, M.; Hellsten, Y.; Hansen, M.; Melin, A.; Kjær, M.; Burr, J. F.; Engebretsen, L.; Egan, B.; Hackney, A. C.; Chambers, T. L.; Jones, A. M.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The International Consensus Conference "Optimising Performance of the Elite Athlete," held in November 2024, brought together 29 scientists, some coaches, and athletes to establish evidence-based consensus statements aimed at enhancing elite athletic performance and health. The conference addressed critical themes including training strategies, nutrition, female athlete considerations, injury management, and emerging technologies. Key conclusions emphasize individualized, sport-specific approaches to training and nutrition, integrating concurrent training modalities to improve endurance, resilience, and efficiency. Nutrition strategies highlight the importance of tailored energy and macronutrient periodization, recognition of low energy availability risks, and cautious use of dietary supplements. Special attention was directed to female athletes, advocating for improved monitoring of menstrual cycles and hormonal status, while acknowledging current knowledge gaps in hormonal influences on performance and injury risk. Injury prevention remains a challenge, with tendon overuse and Achilles tendon ruptures significantly impacting athlete careers; rehabilitation should rely on criteria-based progression and multidisciplinary input. Emerging technologies, including wearable sensors and multi-omics analyses, hold promise for personalized training and nutrition but require further validation in elite contexts. Despite robust consensus, the panel identified substantial research gaps, particularly regarding female athletes, longitudinal training effects, and efficacy of novel interventions. This consensus provides a practical, scientifically grounded framework to optimize elite athlete performance and health, while underscoring the need for continued research to address outstanding questions and promote inclusive evidence-based practices.